Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1530/acta.0.0810409
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Steroid and Protein Hormone Concentrations in Patients With Prostatic Carcinoma, Before and During Oestrogen Therapy

Abstract: Plasma testosterone, androstenedione, oestradiol-17β, follicle stimulating hormone (FSH) and luteinizing hormone (LH) were not significantly different in patients with prostatic cancer, with benign prostatic hyperplasia or in patients without prostatic disease. Plasma prolactin concentrations were significantly lower in the patients with benign disease than those with prostatic carcinoma. Endocrine therapy in the form of stilboestrol administration significantly decreased plasma levels of testosterone, oestrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
35
4
3

Year Published

1977
1977
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 0 publications
7
35
4
3
Order By: Relevance
“…In contrast to several previous studies (Harper et al, 1976;Bartsch et al, 1977b;Hammond et al, 1978;Habib, 1980;Saroff et al, 1980;H0isaeter et al, 1982;Zumoff et al, 1982;Ranikko & Adlercreutz, 1983;Hulka et al, 1987), the control group was population-based and prostate cancer was ruled out by digital rectal examination and serum analysis for prostate-specific antigen. Serum samples were drawn, stored and analysed according to highly standar- dised routines.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In contrast to several previous studies (Harper et al, 1976;Bartsch et al, 1977b;Hammond et al, 1978;Habib, 1980;Saroff et al, 1980;H0isaeter et al, 1982;Zumoff et al, 1982;Ranikko & Adlercreutz, 1983;Hulka et al, 1987), the control group was population-based and prostate cancer was ruled out by digital rectal examination and serum analysis for prostate-specific antigen. Serum samples were drawn, stored and analysed according to highly standar- dised routines.…”
Section: Discussionmentioning
confidence: 96%
“…In general such comparisons have given conflicting results. Plasma testosterone levels in patients with prostatic cancer have been reported to be both higher than (Ghanadian et al, 1979;Jackson et al, 1980;Ahluwalia et al, 1981;Drafta et al, 1982), similar to (Young & Kent, 1968;Harper et al, 1976;Bartsch et al, 1977a;Bartsch et al, 1977b;Hammond et al, 1978;Habib, 1980;H0isaeter et al, 1982;Ranikko & Adlercreutz, 1983;Levell et al, 1985;Nomura et al, 1988;Hsing & Comstock, 1989;Barrett-Connor et al, 1990) and lower than (Jackson et al, 1980;Ahluwalia et al, 1981;Hill et al, 1982;Meikle & Stanish, 1982;Zumoff et al, 1982;Levell et al, 1985;Meikle et al, 1985) those in healthy controls. Similarly, conflicting results have been reported for estradiol (Harper et al, 1976;Bartsch et al, 1977a;Bartsch et al, 1977b;Hammond et al, 1978;Jackson et al, 1980;Jacobi et al, 1980;Ahluwalia et al, 1981;Drafta et al, 1982;Hill et al, 1982;H0isaeter et al, 1982;Meikle & Stanish, 1982;Ranikko & Adlercreutz, 1983;Hulka et al, 1987;Nomura et al, 1988;Hsing & Comstock, 1989;…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…21 Recently Harper et a1. 22 concluded that the LH, FSH and testosterone levels were within normal range in the cancer patients. Tissue culture experiments have shown that the growth of cancer cells was not androgen dependent. "…”
Section: Discussionmentioning
confidence: 96%
“…The PRL receptors are detected in benign prostate hyperplasia and highly synthesized in dysplasia, but only slightly in higher-grade carcinomas (Leav et al 1999). A high blood concentration of PRL in some prostate cancer patients has been reported (Harper et al 1976, Horti et al 1998. Although Stattin et al (2001) have established only a slight correlation between hyperprolactinemia and increased risk of prostate cancer in men, Ben-Jonathan et al (2002) recently reported that PRL increases prostate weight and promotes development of dysplasia and adenocarcinoma of the dorsolateral lobe of the rat prostate.…”
Section: Discussionmentioning
confidence: 99%